Processing of clustered DNA damage generates additional double-strand breaks in mammalian cells post-irradiation. - Gulston, M; de Lara, C; Jenner, T; Davis, E; O'Neill, P (2004)
Clustered DNA damage sites, in which two or more lesions are formed within a few helical turns of the DNA after passage of a single radiation track, are signatures of DNA modifications induced by ionizing radiation in mammalian cells. Mutant hamster cells (xrs-5), deficient in non-homologous end joining (NHEJ), were irradiated at 37 degrees C to determine whether any additional double-strand breaks (DSBs) are formed during processing of gamma-radiation-induced DNA clustered damage sites. A class of non-DSB clustered DNA damage, corresponding to approximately 30% of the initial yield of DSBs, is converted into DSBs reflecting an artefact of preparation of genomic DNA for pulsed field gel electrophoresis. These clusters are removed within 4 min in both NHEJ-deficient and wild-type CHO cells. In xrs-5 cells, a proportion of non-DSB clustered DNA damage, representing approximately 10% of the total yield of non-DSB clustered DNA damage sites, are also converted into DSBs within approximately 30 min post-gamma but not post-alpha irradiation through cellular processing at 37 degrees C. That the majority of radiation-induced non-DSB clustered DNA damage sites are resistant to conversion into DSBs may be biologically significant at environmental levels of radiation exposure, as a non-DSB clustered damage site rather than a DSB, which only constitutes a minor proportion, is more likely to be induced in irradiated cells.